Highly Strained, Radially π-Conjugated Porphyrinylene Nanohoops - Xu, Youzhi; Gsänger, Sebastian; Minameyer, Martin; Imaz, Inhar; Maspoch, Daniel; Shyshov, Oleksandr; Schwer, Fabian; Ribas, Xavi; Drewello, Thomas; Meyer, Bernd; Von Delius, Max (Journal of the American Chemical Society, 2019)
Small π-conjugated nanohoops are difficult to prepare, but offer an excellent platform for studying the interplay between strain and optoelectronic properties, and, increasingly, these shape-persistent macrocycles find uses in host-guest chemistry and self-assembly. We report the synthesis of a new family of radially π-conjugated porphyrinylene/phenylene nanohoops. The strain energy in the smallest nanohoop [2]CPT is approximately 54 kcal mol-1, which results in a narrowed HOMO-LUMO gap and a red shift in the visible part of the absorption spectrum. Because of its high degree of preorganization and a diameter of ca. 13 Å, [2]CPT was found to accommodate C60 with a binding affinity exceeding 108 M-1 despite the fullerene not fully entering the cavity of the host (X-ray crystallography). Moreover, the π-extended nanohoops [2]CPTN, [3]CPTN, and [3]CPTA (N for 1,4-naphthyl; A for 9,10-anthracenyl) have been prepared using the same strategy, and [2]CPTN has been shown to bind C70 5 times more strongly than [2]CPT. Our failed synthesis of [2]CPTA highlights a limitation of the experimental approach most commonly used to prepare strained nanohoops, because in this particular case the sum of aromatization energies no longer outweighs the buildup of ring strain in the final reaction step (DFT calculations). These results indicate that forcing ring strain onto organic semiconductors is a viable strategy to fundamentally influence both optoelectronic and supramolecular properties.
CRIS-Team Scopus Importer:2019-11-26